A performance‐based measure of emotion response control: A preliminary MRI study. Issue 3 (6th January 2021) - Steinert, Steven W.; Daugherty, Ana M.; Shankar, Sneha; Schwarb, Hillary; Cerjanic, Alex; Sutton, Bradley P.; Arble, Eamonn P.
Abstract : Identifying performance‐based assessments of emotion regulation is needed for the study of myriad mood and neurological disorders. Color and form responses on the Rorschach Inkblot Method are valid measures of emotion response control, but have not been studied in relation to known neural correlations of emotion regulation. A discrepancy of color (CF + C) greater than form (FC) responses suggests low cognitive control over emotional responses. This preliminary report explores the discrepancy between form‐color responses as a correlate of regional cortical thickness. A sample of community‐dwelling adults were administered the Rorschach Inkblot Method and participated in a structural MRI scan. Greater middle frontal cortex thickness was associated with a positive discrepancy score [(CF + C) – FC], indicating less emotion response control (rs  = 0.48, p  < 0.05); a moderate, non‐significant correlation was also observed with insula cortex (rs  = 0.42, p  = 0.07).The results provide evidence in support of the Rorschach Inkblot Method as a valid behavioral measure of emotion response control. More specifically, these results support the use of color‐related variables included in contemporary evidence‐based Rorschach methods. The results are discussed with implications for the study of emotion regulation in mood disorders and sensitivity analyses based on the observed effect sizes are reported to inform future study planning.